Pelatihan Penulisan Artikel Ilmiah dan Publikasi Jurnal Ilmiah Bagi Guru-Guru di Kabupaten Tuban - Fadiana, Mu'jizatin; Warli, Warli; Sulistyaningrum, Heny; Rahayu, Puji (Dharma: Jurnal Pengabdian Masyarakat, 2021)
This community service activity is motivated by the low ability of teachers to write scientific papers. The purpose of the activity is to increase the ability of teachers to compile scientific articles based on Classroom Action Research (CAR). The method of this activity is in the form of training and mentoring to participants. Training is carried out online through the zoom application, while mentoring is also carried out online through the Telegram Group application. This activity is carried out through 4 stages, including; the preparation stage, the implementation stage, the assistance stage, and the evaluation stage. Instruments to measure the success of the training process and results using questionnaires and evaluation sheets. Based on the data from the community service results, it can be concluded that the knowledge of teachers about writing scientific papers, publication of scientific papers and teacher professionalism has increased. This can be proven by the success of teachers in publishing scientific articles. And there is an effective cooperative relationship between the MGMP and the Mathematics education program FKIP, PGRI Ronggolawe University, Tuban.